2019
DOI: 10.2147/cmar.s196509
|View full text |Cite
|
Sign up to set email alerts
|

<p>NPTX1 promotes metastasis via integrin/FAK signaling in gastric cancer</p>

Abstract: Purpose This study aimed to investigate the effect of NPTX1 on the prognosis of gastric cancer (GC), as well as the metastatic process in GC. Materials and methods The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases were used to analyze the association between NPTX1 expression and prognosis in GC. Quantitative real-time polymerase chain reaction and Western blots were applied to examine the expression of NPTX1 in GC cell lines and expression of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…7a, b). As we know, focal adhesion kinase (FAK), Src, and paxillin are the principal components of the FA complex; the phosphorylation of these proteins was confirmed to be a critical process during the FA complex formation [25][26][27] . Western blot results are shown in Fig.…”
Section: Foxc2-as1 Promotes Crc Progression Via Ca 2+ -Fak Signalingmentioning
confidence: 99%
“…7a, b). As we know, focal adhesion kinase (FAK), Src, and paxillin are the principal components of the FA complex; the phosphorylation of these proteins was confirmed to be a critical process during the FA complex formation [25][26][27] . Western blot results are shown in Fig.…”
Section: Foxc2-as1 Promotes Crc Progression Via Ca 2+ -Fak Signalingmentioning
confidence: 99%
“…[51][52][53][54] Its function in EAC is still unclear and some studies have suggested it plays a role in regulating cell migration 55 and tumor metastasis. 56 ITPR1 is considered as the most prominent gene in regulating cancer cell resistance to NK-mediated lysis 57 and has been shown to be involved in the regulation of intracellular calcium signaling and the regulation of autophagy. 58 in vivo studies have previously indicated that ITPR1 targeting in cancer cells in combination with NK depletion contributed to tumor growth, indicating its role in the regulation of in vivo susceptibility of renal carcinoma cells to NK activities.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion assay was performed as previously described. 16 HGC-27 and MKN-7 cells transfected with FKBP10 siRNA or NC siRNA were seeded in 96-well plates, which were pre-coated with 10 µg/mL Matrigel at 37°C overnight at a density of 1 × 10 4 cells/200 µL. After incubating at 37°C for 30 minutes, wash three times with phosphate buffer saline (PBS) to remove non-adherent cells.…”
Section: Adhesion Assaymentioning
confidence: 99%
“…Western blotting was performed as previously described. 16 Cells were extracted in 1% Triton lysis buffer and quantified using the Coomassie brilliant blue method. Then, the cell lysates were separated by SDS-PAGE and electrophoretically transferred to a polyvinylidene fluoride (PVDF) membrane (Millipore, Bedford, MA, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation